2011
DOI: 10.1111/j.1752-7325.2011.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of oral health quality of life in HIV-1 infected patients attending routine care in Australia

Abstract: Objective: To examine predictors of oral health quality of life (OHQoL) in a human immunodeficiency virus (HIV)‐infected population undergoing routine HIV care in the era of antiretroviral therapy. Method: The study was an anonymous self‐administered survey of 273 patients. Subjects completed the Oral Health Impact Profile‐14 and questionnaires on sociodemographics, HIV, and dental issues. Multiple logistic regression analysis was conducted to determine the predictors of OHQoL. Results: The study found smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
1
8
2
Order By: Relevance
“…We also found that participants with lower personal income had significantly higher S-OHIP(M) scores, indicating more severe oral impact, in agreement with a study of OHRQOL among PLWHA in Sydney, Australia [ 39 ]. Besides income, other studies reported that individual characteristics, such as sex and ethnicity, were significantly associated with the OHRQOL of PLWHA [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…We also found that participants with lower personal income had significantly higher S-OHIP(M) scores, indicating more severe oral impact, in agreement with a study of OHRQOL among PLWHA in Sydney, Australia [ 39 ]. Besides income, other studies reported that individual characteristics, such as sex and ethnicity, were significantly associated with the OHRQOL of PLWHA [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Also, the wearing denture was the only factor with signi cant association with OHRQoL in multiple regression analysis. In contrast, Jeganathan and coworkers study found that the patients wearing a removable denture had worse OHRQoL than those with natural dentition (18). The difference between the results of these studies and our ndings might be because of the high proportion of decayed and bad quality teeth in our patients' mouth that led to oral symptoms.…”
Section: Discussioncontrasting
confidence: 92%
“…Other studies also could not show a signi cant association between the patients' OHRQoL and the following socioeconomic factors: income per capita (8), number of people residing in the family home (8,17), education level (8), children's heightfor-age ratio (2), household ownership (17). In contrast, studies showed worse OHRQoL for the unemployed (4, 7, 15), brown or black people (4), and those with lower education level (7) and lower personal monthly income (6,7,9,10,18). Also, studies showed that the patients with HIV that had adequate social support experienced better OHRQoL (10,17).…”
Section: Discussionmentioning
confidence: 99%
“…identified a significant correlation between OHIP‐49 and smoking status with oral health impacts prevalent among HIV cigarette smokers. Jeganathan et al . looked at the predictors of oral health quality of life in HIV‐1 infected patients and concluded that smoking is a significant predictor which could be targeted to improve quality of life among people living with HIV.…”
Section: Discussionmentioning
confidence: 99%